Project tooth keeper : a children's oral health campaign - Chow, Grace En En (2014)
This paper presents “Project Tooth Keeper”, a health communications campaign by four final year undergraduates at the Wee Kim Wee School of Communication and Information (WKWSCI) in Nanyang Technological University (NTU). The campaign was mounted in response to the declining oral health status of infants and preschoolers in Singapore. Secondary research has revealed that the increasing incidence of tooth decay among infants and preschoolers in Singapore follows a global oral health trend. Insights from paediatric dentists were sought to gather information on the possible causes for the rise, and parents were interviewed on the dental care practices they observe for their children. From this, a quantitative survey was conducted with the purpose of confirming dentists’ opinion that parents’ ignorance about cariogenic behaviours and the importance of children’s baby teeth, have contributed to the decline in the oral health status of Singaporean young children. Based on the survey findings, Project Tooth Keeper was launched to promote good parenting for children’s oral health, targeting parents with children aged six years and under. The campaign set out to educate parents on and motivate them by stressing the importance and benefits of preventive oral health behaviours in preventing the onset of tooth decay in a child’s life. Through education and motivation, Project Tooth Keeper aims to ultimately increase parents’ intention to carry out preventive oral health behaviours for their children.